THE RELATIONSHIPS BETWEEN GENDER-NEUTRAL PARENTING ATTITUDES, NEGATIVE DIMENSIONS OF SEXUAL ORIENTATION IDENTITY, AND CHILD OUTCOMES AMONG LESBIAN MOTHERS - Alligood, Brittany (East Carolina University, 2020)
The primary purpose of this study was to explore the correlations between lesbian mothers' gender-neutral parenting attitudes, negative dimensions of their sexual orientation identity, and child outcomes. Participants included lesbian mothers (N = 40) with at least one child between the ages of 3 and 8 years-old. Among mothers, 37.5% completed the questionnaire from the perspective of their male-identified child (n = 15), while 62.5% completed the questionnaire from the perspective of their female-identified child (n = 25). To measure the constructs of interest, participants were assessed via an online survey using three instruments, the Child Gender Socialization Scale, the Lesbian, Gay, and Bisexual Identity Scale, and the Strengths and Difficulties Questionnaire. Four open-ended response questions were additionally analyzed to better support the results. Results indicated factors such as the sex of the child, education level, and internalized homonegativity can play a significant role on gender-neutral parenting attitudes and child outcomes among lesbian mothers. Implications regarding genderneutral parenting practices and research on lesbian mothers are further discussed.
Keywords: gender-neutral; early childhood; Lesbian mothers--Attitudes; Parenting; Child development; Gender identity